2019
DOI: 10.1038/s41419-019-1782-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signaling pathways in Sertoli cells: recent findings in spermatogenesis

Abstract: The functions of Sertoli cells in spermatogenesis have attracted much more attention recently. Normal spermatogenesis depends on Sertoli cells, mainly due to their influence on nutrient supply, maintenance of cell junctions, and support for germ cells’ mitosis and meiosis. Accumulating evidence in the past decade has highlighted the dominant functions of the MAPK, AMPK, and TGF-β/Smad signaling pathways during spermatogenesis. Among these pathways, the MAPK signaling pathway regulates dynamics of tight junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 178 publications
2
99
0
Order By: Relevance
“…From a metabolic perspective, we observed that once a cell enters Stage_b, its preferred metabolic pathway changes from oxidative phosphorylation to glycolysis. This is consistent with the previous observation that lactic acid (produced by glycolysis) provides energy for germ cell development 26 . It is worth noting that all three stages of Sertoli cells exist and form a steady state in adult testes, maintaining the basic structure of seminiferous tubules and also guaranteeing homeostasis of the microenvironment for spermatogenesis for decades.…”
Section: Discussionsupporting
confidence: 93%
“…From a metabolic perspective, we observed that once a cell enters Stage_b, its preferred metabolic pathway changes from oxidative phosphorylation to glycolysis. This is consistent with the previous observation that lactic acid (produced by glycolysis) provides energy for germ cell development 26 . It is worth noting that all three stages of Sertoli cells exist and form a steady state in adult testes, maintaining the basic structure of seminiferous tubules and also guaranteeing homeostasis of the microenvironment for spermatogenesis for decades.…”
Section: Discussionsupporting
confidence: 93%
“…The overall mortality rate is estimated to be 2.3% (1023 deaths among 44,762 confirmed cases of COVID-19), based on experience within China [67]. Compared with greater than 10% mortality of SARS-CoV [68] and 35% mortality of MERS-CoV [69], SARS-Cov-2 has a lower mortality rate but appears to be more contagious. The mortality rate may be even lower in the realworld setting once the infection has stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is characterized by large changes in the energy requirement and the availability of substrates at each stage of sperm differentiation. Spermatogoniawhich lie close to the basal membranedepend on blood glucose to fuel glycolytic processes, whilst later stage spermatocytes and spermatidslocated deeper within the testisrequire lactate secreted by Sertoli cells [75,76]. In contrast, spermatozoa are more adaptable on which substratesfor example glucose, fructose and pyruvatethey use for their energy metabolism, which is believed to be an adaptation to the varying availability of substrates in the male and female reproductive tracts [77][78][79][80][81].…”
Section: Dynamic Changes Of Sperm Sncrna During Spermatogenesismentioning
confidence: 99%